Relationship between research and development management and gross domestic product of Peru - Miraval-Fonseca, Rosaura M. (2023)
Objective. Determine theoretically and empirically the theories that corroborate the relationship between research management, development and the gross domestic product of Peru, adapting it to the Peruvian structure led by the INIA based on the Joseph Stiglitz model within the framework of the national innovation system. Methods. A quantitative, explanatory, and cross-sectional study was carried out, the sample represented is from the statistics of the research and development management database, analyzed in the variables of productive scientific knowledge and value-added production of a total of 512 publications in SCOPUS of the variables dating from the period 2000–2020, the assessment was according to Joseph Stiglitz. Document analysis techniques were used, extracting data from the World Bank, BCRP, SCOPUS and RICYT, the data were analyzed with E-Views, Stata, Vosviewer, and Ucinet programs; The level of significance established was p-value (Prob) less than 0.05. Results. The findings showed that research and development (R&D) management explains Peru's gross domestic product by 96%. Meanwhile, value-added production explains 89% of the gross domestic product and productive scientific knowledge 67%, which indicates that they are statistically significant. Conclusions. Human capital management, research development (R&D) and innovation, processes are determinants of technically efficient production processes from all perspectives. However, in the Peruvian case, such a process has little technical consistency to penetrate competitive markets due to the poor impact of the management of productive scientific knowledge.